New species of Cirratulidae (Annelida, Polychaeta) from abyssal depths of the Clarion-Clipperton Fracture Zone, North Equatorial Pacific Ocean - Blake, James A. (Zootaxa, 2019)
Abyssal polychaetes of the family Cirratulidae were collected as part of reconnaissance and benthic impact experimental surveys at Clarion-Clipperton Fracture Zone manganese nodule sites in 1984 and 1993–1994. All specimens were collected from the 4500–4900 m depth range. Twelve species of Cirratulidae were identified, of which 11 are new to science. Aphelochaeta abyssalis n. sp., A. clarionensis n. sp., A. clippertonensis n. sp., A. spargosis n. sp., A. tanyperistomia n. sp., A. wilsoni n. sp., Caulleriella bathytata n. sp., Chaetozone akaina n. sp., C. grasslei n. sp., C. truebloodi n. sp. and Tharyx hessleri n. sp. Most of these species are small deposit-feeding threadlike worms that reside in the upper 5 cm of the sediment and represent a unique assemblage of abyssal taxa.